The ironwood tree - DiTerlizzi, Tony.; Black, Holly (New York Simon & Schuster Books for Young Readers, 2004)
After Mallory is kidnapped at her fencing meet, Jared and Simon search for her near an old quarry and find themselves amidst dwarves and goblins.
Sequel to: The wrath of Mulgarath.
Keywords: Dwarfs -- Fiction; Goblins -- Fiction; Brothers and sisters -- Fiction; Twins -- Fiction; Caves -- Fiction